Web Penetration Testing with Kali Linux: Explore the Methods and Tools of Ethical Hacking with Kali Linux - Dieterle, Daniel W; Najera-Gutierrez, Gilberto; Ansari, Juned Ahmed (Packt Publishing, Limited, 2018)
This book covers everything you need to set up a Kali Linux lab, the latest generation of the BackTrack Linux penetration testing and security auditing Linux distribution. Learn how to use the hundred tools Kali Linux has so you can manage security tasks such as penetration testing, forensics, and reverse engineering.